Analysis of the influencing mechanism of low-frequency alternating magnetic field-assisted freezing on oxidative and structural attributes of pork myofibrillar proteins based on proteomic changes - Zhu, Mingming; Jiang, Lijie; Liu, Wang; Li, Huijie; Jiao, Lingxia; Ma, Hanjun; Gao, Xueli; Kang, Zhuangli (Food chemistry, 2025)
Using quantitative proteomics, the study investigated the effects of low-frequency alternating magnetic field-assisted freezing (LF-MFF) on the oxidative status and structural integrity of porcine myofibrillar proteins (MPs). LF-MFF, especially at 3 mT (LF-MFF-3) and 4 mT (LF-MFF-4), significantly reduced MPs' oxidation compared to refrigerator freezing (RF) (P < 0.05). The spectroscopic analysis confirmed better structural preservation with LF-MFF-4. We identified 126 differentially abundant proteins (DAPs) associated with key metabolic pathways, including amino acid biosynthesis and oxidative phosphorylation, potentially affecting Adenosine Triphosphate (ATP) metabolism and contributing to freeze-induced protein damage and oxidative denaturation of MPs. Through correlation analysis, among the 52 DAPs in the LF-MFF-4 vs RF comparison, eight proteins with variable importance in projection (VIP) > 1.1 were identified as potential biomarkers for porcine MPs. These findings enhance our understanding of the oxidative and structural changes in MPs following LF-MFF, suggesting its potential for improving pork quality and meat preservation. [Display omitted] •LF-MFF-4 preserved MPs' structural integrity by mitigating oxidative denaturation.•Identified 126 DAPs linked to key pathways, potentially impacting ATP metabolism.•Correlation analysis and VIP score identified eight proteins as biomarkers for MPs.